Probability Distribution of Intensity Attenuations for Colombia and Western Venezuela - Prieto Salazar, Jorge Alonso; Foschi, Ricardo O.; Ventura, Carlos E.; Finn, W. D. Liam; Ramos, Alfonso Mariano; Prada, Felipe (GeoScienceWorld, 2011)
This paper presents a database of isoseismal maps and referenced/ processed (isoseismal contour areas and equivalent radii) data for Colombia and neighboring regions based on earthquakes occurring between 1766 and 2004. The database is used to develop a model for the conditional exceedence probability of a level of seismic intensity, given distance to a site and the epicentral intensity. The model comprises mixed discrete–continuous joint probability distributions. The conditional distribution of distance for a given intensity or intensity difference is continuous and is represented by a lognormal distribution. The distribution of intensities is discrete and is represented by bimodal Poisson functions. The bimodal representation may be due to wave reflections at the boundary between the lithosphere and the asthenosphere in the region. Bayes theorem is used to integrate the continuous and discrete distributions to provide the conditional exceedence probabilities of intensity, given distance and epicentral intensities. Two separate models are proposed, one for shallow, crustal events with depths less than 40 km and the second for subduction events. The models are applied to Colombia and western Venezuela.

Este trabajo presenta una base de datos de mapas isosísmicos y datos referenciados/procesados (áreas de contorno isosísmico y radios equivalentes) para Colombia y regiones vecinas basados en terremotos ocurridos entre 1766 y 2004. La base de datos se utiliza para desarrollar un modelo para la probabilidad condicional de excedencia de un nivel de intensidad sísmica, dada la distancia a un sitio y la intensidad epicentral. El modelo comprende distribuciones de probabilidad conjuntas discretas-continuas mixtas. La distribución condicional de la distancia para una intensidad dada o una diferencia de intensidad es continua y está representada por una distribución lognormal. La distribución de las intensidades es discreta y se representa mediante funciones de Poisson bimodales. La representación bimodal puede deberse a las reflexiones de las ondas en el límite entre la litosfera y la astenosfera de la región. Se utiliza el teorema de Bayes para integrar las distribuciones continua y discreta y obtener las probabilidades condicionales de superación de la intensidad, dadas la distancia y las intensidades epicentrales. Se proponen dos modelos distintos, uno para los eventos superficiales de la corteza con profundidades inferiores a 40 km y el segundo para los eventos de subducción. Los modelos se aplican a Colombia y al oeste de Venezuela.
Keywords: Sismometría; Seismometry; Terremotos; Earthquakes; Evaluación de riesgos; Risk assessment